De la casquette de Charles dans les traductions portugaises de Madame Bovary - Luís Carlos Pimenta Gonçalves (Association Portugaise d'Etudes Françaises, 2021)
The purpose of this article is to analyze comparatively eleven Portuguese translations of a passage of Madame Bovary, the description of Charles' cap, a bravura piece of work by Gustave Flaubert who wanted to write "a book about nothing (...) which would be held together by the strength of its style”. This force of style has of course made the translator's task more delicateand this extract reveals the difficulties, the dead ends, the approximations, but also the discoveries, the successes which make translation as much a technique with its procedures as an art where the part of intuition signals both the métier and the talent. Thus, the language of the target text transforms and adapts the source text by using lexical borrowings, improbable equivalences, deletions, even translation notes which are too often admissions of helplessness and renunciation in the face of irreducible linguistic and cultural specificities.